PENGARUH PENDEKATAN STEAM (SCIENCCE, TECHNOLOGY, ENGINEERING, ARTS AND MATHEMATICS) TERHADAP KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK SD/MI - Fadiatul Humairoh; Farida Nur Kumala; Arnelia Dwi Yasa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students' creative thinking skills are currently generally inadequate because the teaching methodology in many elementary schools does not support the development of these abilities. This study aims to examine how the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach affects the creative thinking skills of students at Mergosono 2 Elementary School. This study used a quantitative approach with a quasi-experimental design with a non-equivalent control group design. The sample consisted of 20 students from the experimental class with the STEAM approach and 22 students from the control class with the expository approach. Pretest-posttest essay questions were used to collect data, and an independent t-test was used for data analysis. The results showed a value (sig. 2-tailed) with a total of (0.000) < 0.05, which means that the STEAM approach has an impact on students' creative thinking skills. The average score for the posttest of the experimental class, which used the STEAM approach, was 51.95, while the average score for the posttest of the control class, which used the expository approach, was 35.59.